The magnetotlluric phase tensor method for imaging the north Anatolian fault zone - Bekin, Ekrem. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2016., 2016)
Magnetotelluric data often suffer from localized (three-dimensional) heterogeneities by a real and frequency independent phenomenon known as “galvanic distortions”. There have been numerous techniques developed for avoiding the galvanic distortions and thus, determining the dimensionality of the observed data. Groom and Bailey’s decomposition and the phase tensor analyses are used for avoiding galvanic distortions and Swift’s analysis, Bahr’s parameters are some of the most common and conventional dimensionality determination approaches. The phase tensor is a relatively more recent approach compared to the rest and is useful for studying in a distortion-free medium. The main objective of this study is to develop MATLAB® scripts for calculating and imaging the phase tensor ellipses and applying them to observed data collected at the central part of the North Anatolian Fault Zone (NAFZ). Final images are compared to other geophysical study results performed within the same area.
Keywords: Magnetotelluric prospecting -- Turkey.